2011
DOI: 10.1098/rsif.2011.0188
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary optimization of material properties of a tropical seed

Abstract: Here, we show how the mechanical properties of a thick-shelled tropical seed are adapted to permit them to germinate while preventing their predation. The seed has evolved a complex heterogeneous microstructure resulting in hardness, stiffness and fracture toughness values that place the structure at the intersection of these competing selective constraints. Analyses of different damage mechanisms inflicted by beetles, squirrels and orangutans illustrate that cellular shapes and orientations ensure damage resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 39 publications
0
39
0
1
Order By: Relevance
“…Likely candidates for such small, hard items are the seeds of African grasses and sedges, although the material properties of these grains have not previously been well documented. Accordingly, we performed mechanical tests on seeds gathered from African habitats (see Appendix) and found that their indentation hardness and material stiffness (i.e., elastic modulus) (Table ) are broadly comparable to those of much larger nut and seed shells (Lucas et al, 2009, ). Grass seed consumption would entail highly repetitive loading, because the seeds are individually so small that many would need to be eaten in order to provide a meaningful source of nutrition.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Likely candidates for such small, hard items are the seeds of African grasses and sedges, although the material properties of these grains have not previously been well documented. Accordingly, we performed mechanical tests on seeds gathered from African habitats (see Appendix) and found that their indentation hardness and material stiffness (i.e., elastic modulus) (Table ) are broadly comparable to those of much larger nut and seed shells (Lucas et al, 2009, ). Grass seed consumption would entail highly repetitive loading, because the seeds are individually so small that many would need to be eaten in order to provide a meaningful source of nutrition.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is worth bearing in mind that the mechanical properties of hard foods vary considerably and thus pose different challenges to the hominins consuming them. For example, the material stiffness (as measured by the elastic modulus) of corms and bulbs (Dominy et al, ) is roughly three orders of magnitude less than that of seed and nut shells (Table ; Lucas et al, 2009, ). Thus, corms and bulbs mechanically resemble seed kernels, rather than seed coats.…”
Section: Discussionmentioning
confidence: 99%
“…Bornean orangutans spend much of the year eating unripe fruits and hard seeds, such as the seeds of Mezzettia parviflora at Tuanan and Lithocarpus (Fagaceae) at Ganung Palung (Galdikas 1982;Vogel et al 2008). The elastic modulus of many parts of the seed shell of Mezzettia exceeds 7 GPa (Lucas et al 1994;2012) highlighting these seeds as likely culprits of chip causation. In contrast, the vast majority of orangutan foods at Tuanan have maximum elastic modulus values <9 MPa (Vogel et al 2008).…”
Section: Chipping Frequencymentioning
confidence: 98%
“…Dust particles can be smaller [54] and chips very much larger [17,42], but our model nevertheless predicts that the forces involved in micro-feature formation are tiny compared with the bite force maxima of mammals. Orangutans, whose enamel was used in these experiments, can produce bite forces of 2000 N [55], giving capacity for thousands of scratches, grooves, troughs or pits from just rsif.royalsocietypublishing.org J R Soc Interface 10: 20120923 one chew were particles to be present in large quantity. The saving grace is that quartz is probably only ingested in small quantities by mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Phytoliths in themselves do not seem to provide a clear dietary guide to plant parts, insofar as many leaves and seeds contain them [34]. Moreover, it is unlikely that non-siliceous plant components like seed shells could abrade enamel [62], given that they have only 10 per cent of the hardness of enamel at most [55]. Their consumption would likely be hidden from microwear analysis.…”
Section: Discussionmentioning
confidence: 99%